PENERAPAN KITAB TARBIYAH AL-AULÃD FĨ AL-ISLÃM KARYA ABDULLAH NASHIH ULWAN DALAM MENDIDIK ANAK DI ERA DIGITAL - Hidayat, Galuh Krisnawati; Subekti, M. Yusuf Agung (Journal Islamic Studies, 2022)
Many parents underestimate the education of children. Parents prefer to give gadgets to their children rather than nurture and educate directly so that children are free to access everything without any supervision by parents. This study aims to expand alternative solutions to the problems of children's education in the digital era seen and reviewed in an Islamic perspective by Tarbiyah Al-Aulãd Fĩ Al-Islãm’ book . This research uses a type of library research , which is a type of research carried out using a literature. With a qualitative descriptive approach where the data obtained will be described. The results in this research (1) Children's education according to Abdullah Nashih Ulwan's perspective includes 7 aspects (2) The problems of children's education in digital era according to Abdullah Nashih Ulwan’s perspective in the current review have 4 factors (3) Implementation of solutions to children's education problems in the digital era according to Abdullah Nashih Ulwan have 5 metods.